Unveiling the Mechanisms of Change: An Explanatory Case Study of Improving Hip Fracture Rehabilitation in Sweden - Susanne Löfgren; Leif Ryd; Carolina Wannheden; Mats Brommels (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2016)
Background: Hip fracture has a high risk of mortality and puts a large financial burden on the health care system.  Context and Purpose: A successful hip fracture rehabilitation project at a Swedish university hospital resulted in reduced length of hospital stay, earlier returns to pre-accident housing, and decreased costs. The purpose was to identify promoters and obstacles of change in the improvement project.  Methods: This is an explanatory case study of a hip fracture improvement project. Pettigrew and Whipp's framework was used for describing the four strategic dimensions of change in the case: context, content, process, and outcomes. Mixed methods data was used to identify promoters and obstacles. Findings: Promoters: a dedicated project leader, empowerment educated rehabilitation staff, the combination of planned and emergent change; co-location of orthopaedic surgery and geriatric rehabilitation ward. Obstacles: organizational complexity, resistance to change.  Conclusions: A dedicated project leader supported by top management and the use of empowerment in the rehabilitation in combination with planned and emergent change can lead to improvement, despite organizational complexity and resistance to change. Potential implications: This study provides a better understanding of promoters and obstacles of change that influenced the success of a hip fracture improvement project in a large health care organization. This knowledge may support decision makers when planning large-scale improvement projects in complex organizations.